2017
DOI: 10.1177/2333393617696686
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting the Functional Processes of Apologizing for Errors in Health Care

Abstract: This article has been awarded GQNR’s Best Paper Award for the 2017 Volume The purpose of this article was to analyze the concept development of apology in the context of errors in health care, the administrative response, policy and format/process of the subsequent apology. Using pragmatic utility and a systematic review of the literature, 29 articles and one book provided attributes involved in apologizing. Analytic questions were developed to guide the data synthesis and types of apologies used in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…One important strategy is for the nurse to apologize to the person whose care is being interrupted. Previous research has shown providing a full apology to a patient when a medical error occurs restores the relationship and minimized legal ramifications (Prothero & Morse, 2017). Interestingly, very few studies have looked at how apologizing to patients for an error or inconvenience impacts their perception of care.…”
Section: Discussionmentioning
confidence: 99%
“…One important strategy is for the nurse to apologize to the person whose care is being interrupted. Previous research has shown providing a full apology to a patient when a medical error occurs restores the relationship and minimized legal ramifications (Prothero & Morse, 2017). Interestingly, very few studies have looked at how apologizing to patients for an error or inconvenience impacts their perception of care.…”
Section: Discussionmentioning
confidence: 99%
“…Written apologies should not replace verbal apologies. 42 Participants had anticipated their justice needs would be met through human connectionto be listened to and heardbut instead found the investigation focused on written facts, truth-finding and accusation. Notwithstanding the technical status of the Commissioner's opinion being, for the most part, legally inconsequential, 5 importance on the authority of the decision due to potential disciplinary action and the impact on reputation and livelihood.…”
Section: Discussionmentioning
confidence: 99%
“…. " allows us to bring solace to the patient [12]. Some physicians are reticent to use such expressions, perhaps for fear of having them viewed as admissions of error and, as a result, causes for medico-legal reprisals [13].…”
Section: Apologizingmentioning
confidence: 99%
“…Sincere apologies are excellent tools to defuse a crisis and to win back a patient’s sympathy. “I am sorry that…” or “I am sorry for…” allows us to bring solace to the patient [ 12 ]. Some physicians are reticent to use such expressions, perhaps for fear of having them viewed as admissions of error and, as a result, causes for medico-legal reprisals [ 13 ].…”
Section: Principles Of Crisis Managementmentioning
confidence: 99%